Dm3 Is One Member of a Large Constitutively Expressed Family of Nucleotide Binding Site—Leucine-Rich Repeat Encoding Genes - Katherine A. Shen; Doris B. Chin; Rosa Arroyo-Garcia; Oswaldo E. Ochoa; Dean O. Lavelle; Tadeusz Wroblewski; Blake C. Meyers; Richard W. Michelmore (Molecular Plant-Microbe Interactions, 2002)
The major cluster of resistance genes in lettuce cv. Diana contains approximately 32 nucleotide binding site—leucine-rich repeat encoding genes. Previous molecular dissection of this complex region had identified a large gene, RGC2B, as a candidate for encoding the downy mildew resistance gene, Dm3. This article describes genetic and transgenic complementation data that demonstrated RGC2B is necessary and sufficient to confer resistance with Dm3 specificity. Ethylmethanesulphonate was used to induce mutations to downy mildew susceptibility in cv. Diana (Dm1, Dm3, Dm7, and Dm8). Nineteen families were identified with a complete loss of resistance in one of the four resistance specificities. Sequencing revealed a variety of point mutations in RGC2B in the six dm3 mutants. Losses of resistance were due to single changes in amino acid sequence or a change in an intron splice site. These mutations did not cluster in any particular region of RGC2B. A full-length ge-nomic copy of RGC2B was isolated from a lambdaphage library and introduced into two genotypes of lettuce. Trans-genics expressing RGC2B exhibited resistance to all isolates expressing Avr3 from a wide range of geographical origins. In a wildtype Dm3-expressing genotype, many of the RGC2 family members are expressed at low levels throughout the plant.